A nanoemulsion vitamin D3 drop and a preparation method thereof
Patent Information
- Application Number
- CN202611358898.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-03
- Publication Date
- 2026-10-30
AI Technical Summary
[0008]本发明针对现有维生素D3滴剂粒径不均、稳定性差、有效成分易氧化、生物利用度低、批次一致性差的技术缺陷,提供一种纳米乳维生素D3滴剂及其制备方法
(1)本发明创新性采用中链甘油三酯与油酸乙酯按2:1-3:1复配作为复合油相,相较于单一植物油油相或单一MCT油相,兼具优异的脂溶性溶解能力与水相适配性,可大幅提升维生素D3溶解度,同时降低油水界面张力;复配聚甘油-4油酸酯与吐温80按1.5:1-2:1作为复合乳化剂,协同实现纳米乳高包封效果;复配维生素E与柠檬酸按3:1作为抗氧化稳定剂,维生素E作为链终止型抗氧化剂清除自由基,柠檬酸作为金属离子螯合剂防止金属离子催化氧化,两者协同实现长效抗氧化保护。
Smart Images

Figure RYQTVGBWRCPON9LBYS13FY12K6GEFETBMAVPCK9U 
Figure SPVGZZ11JWFOALQOYDCKE9BYUKNTF9FGDPP9VMAQ
Abstract
Description
Technical Field
[0001] This invention belongs to the field of functional pharmaceutical drops preparation technology, specifically relating to a nanoemulsion vitamin D3 drop and its preparation method. Background Technology
[0002] Vitamin D3 (cholecalciferol) is an essential fat-soluble vitamin for the human body. Its core functions include regulating calcium and phosphorus metabolism, promoting bone development, and enhancing the body's immunity. Deficiency in children can easily lead to rickets, while deficiency in adults can result in osteoporosis, weakened immunity, and other health problems. With increasing emphasis on nutrition and health, the market demand for vitamin D3 supplements continues to grow.
[0003] Currently, most mainstream vitamin D3 drops on the market are either ordinary oil-soluble or conventional emulsion formulations. Both of these formulations have different degrees of technical defects: (1) Vitamin D3 is extremely lipid-soluble and extremely water-soluble. Ordinary oil-soluble drops have poor dispersibility and slow dissolution rate in the aqueous gastrointestinal environment, resulting in low absorption and utilization rate by the human body and a relatively high clinical dosage. (2) Conventional emulsions have particle sizes mostly in the micrometer range, resulting in poor system stability. Long-term storage can easily lead to problems such as layering, precipitation, and vitamin D3 oxidation degradation, and the content of effective ingredients will seriously decrease within the shelf life. (3) Traditional preparation processes mostly use single high-speed shear emulsification, resulting in uneven emulsification, low nano-forming rate, wide particle size distribution and poor uniformity of the finished product, making it difficult to guarantee batch stability.
[0004] Among the publicly available technologies, CN103520102A discloses a vitamin D nanoemulsion composed of vitamin D, Tween-80 in a mass ratio of 1:(1-6), and water, prepared by ultrasonic emulsification. This formulation is overly simple, relying solely on the single emulsifier Tween-80, lacking an antioxidant protection system to address the easily oxidized properties of vitamin D3, and the ultrasonic emulsification method is difficult to implement for large-scale industrial production.
[0005] CN113498344A discloses a vitamin D nanoemulsion and its uses, wherein the particle size of the emulsion particles is 100-300 nanometers. This scheme has a relatively large particle size and is mainly aimed at ocular drug delivery, without addressing the optimization of stability and bioavailability of oral drop formulations.
[0006] Existing technologies also include reports on the preparation of vitamin D nanoemulsions using fragmented corn protein-tannic acid complexes as emulsifiers, and schemes for preparing fat-soluble component nanoemulsions using caprylic / capric triglycerides and sodium octenyl succinate starch. However, none of these technical solutions systematically optimize the formulation system and gradient preparation process to address the characteristics of vitamin D3, such as easy oxidation, poor water solubility, and difficulty in nanoforming. They generally suffer from poor controllability of nanoparticle size, insufficient long-term thermal stability, and low bioavailability.
[0007] In summary, existing technologies lack synergistic formulation design of composite oil phase and composite emulsifier targeting the characteristics of vitamin D3, lack antioxidant stabilizer compounding system, and lack nano-preparation process that couples gradient high pressure homogenization and high speed shearing. As a result, it is impossible to achieve large-scale preparation of nanoemulsion droplets with small particle size, narrow distribution, high stability, and high encapsulation efficiency. Summary of the Invention
[0008] This invention addresses the technical shortcomings of existing vitamin D3 drops, such as uneven particle size, poor stability, easy oxidation of active ingredients, low bioavailability, and poor batch consistency, by providing a nanoemulsion vitamin D3 drop and its preparation method.
[0009] This invention utilizes an innovative compound formulation system of composite oil phase, composite emulsifier, and antioxidant stabilizer, combined with high-speed shear crude emulsion preparation, two-stage gradient high-pressure microfluidic homogenization coupling process, and full-process nitrogen inert gas protection, to prepare nanoemulsion vitamin D3 drops with uniform particle size, high encapsulation rate, excellent stability, and significantly improved bioavailability. At the same time, the preparation process of this invention is simple and applicable to large-scale production.
[0010] The technical solution of this invention is: A method for preparing nanoemulsion vitamin D3 drops, wherein the drops comprise the following raw materials in parts by weight: Vitamin D3 0.05-0.2 parts, compound oil phase 8-15 parts, compound emulsifier 4-8 parts, co-emulsifier 1-3 parts, antioxidant stabilizer 0.2-0.8 parts, pH adjuster 0.1-0.3 parts, purified water to 100 parts; The preparation method of this nanoemulsion vitamin D3 drops includes the following steps: S1. Preparation of oil phase: The composite oil phase is preheated and stirred in a constant temperature water bath at 40-45℃ for 5-8 minutes at a stirring speed of 300 r / min. After the system is completely homogeneous and transparent, vitamin D3 and antioxidant stabilizer are added, and the mixture is stirred continuously at a constant temperature in the dark for 10-15 minutes until vitamin D3 is completely dissolved to obtain the oil phase. Nitrogen inert gas protection is used throughout the process. S2. Preparation of aqueous phase: Take purified water and heat it to 35-40℃. Add composite emulsifier, co-emulsifier and pH adjuster. Stir at a constant temperature for 8-10 minutes at a stirring speed of 400r / min until all excipients are completely dissolved and the system is clear and transparent to obtain the aqueous phase. S3. Preparation of crude emulsion: The oil phase prepared in step S1 is slowly added dropwise to the aqueous phase in step S2 over a period of 15-20 min. During the addition process, high-speed shear dispersion is used with a shearing speed of 12000-15000 r / min. After the addition is completed, shearing is continued for 8-12 min to obtain crude emulsion. S4. Gradient homogenization and nano-sizing treatment: The crude emulsion is subjected to two-stage high-pressure micro-jet homogenization treatment. The first-stage homogenization pressure is 80-100MPa and the homogenization is performed twice. The second-stage homogenization pressure is 140-160MPa and the homogenization is performed three times. The system temperature is controlled at 30-35℃ during the homogenization process to obtain nano-emulsion stock solution. S5. Post-processing and filling: The nanoemulsion stock solution is placed in a light-proof, nitrogen-protected environment and naturally cooled to room temperature. It is then filtered through a 0.22μm sterile microporous membrane for sterilization and quantitative aseptic filling to obtain the finished nanoemulsion vitamin D3 drops.
[0011] In some embodiments, the composite oil phase is a mixture of medium-chain triglycerides and ethyl oleate in a mass ratio of 2:1 to 3:1.
[0012] In some embodiments, the composite emulsifier is a mixture of polyglycerol-4 oleate and Tween 80 in a mass ratio of 1.5:1 to 2:1.
[0013] In some embodiments, the co-emulsifier is propylene glycol.
[0014] In some embodiments, the antioxidant stabilizer is a mixture of vitamin E and citric acid in a mass ratio of 3:1.
[0015] In some embodiments, the criteria for determining whether vitamin D3 is completely dissolved in step S1 are: no particulate matter is found upon visual inspection, or the absorbance is constant when detected by ultraviolet spectrophotometry at 265 nm.
[0016] In some embodiments, the pH adjuster is anhydrous sodium carbonate, and the amount of anhydrous sodium carbonate used is such that the pH value of the system is adjusted to 6.5-7.5.
[0017] In some embodiments, the average particle size of the nanoemulsion vitamin D3 drops is 20-40 nm, the particle size distribution index (PDI) is ≤0.15, and the vitamin D3 encapsulation rate is ≥98.5%.
[0018] In some embodiments, the finished nanoemulsion vitamin D3 drops are stored at 25℃±2℃ in the dark for 18 months, and the vitamin D3 retention rate is ≥96%.
[0019] The nanoemulsion vitamin D3 drops provided by this invention use a composite oil phase made of medium-chain triglycerides (MCT) and ethyl oleate in a ratio of 2:1 to 3:1. MCT can fully dissolve vitamin D3, and its short molecular chain allows for rapid hydrolysis and absorption without bile emulsification. However, MCT alone has a high oil-water interfacial tension and insufficient resistance to Ostwald ripening. Ethyl oleate can reduce the oil-water interfacial tension, and its difference in molecular volume and polarity with MCT can slow down the diffusion rate of oil phase molecules in the aqueous phase, effectively inhibiting droplet size growth. The combination of the two achieves the best balance of solubility, emulsification, and resistance to ripening. The composite emulsifier in the raw materials is a composite of polyglycerol-4 oleate (HLB value 10-12) and Tween 80 (HLB value approximately 15) in a ratio of 1.5:1 to 2:1, supplemented with propylene glycol as a co-emulsifier. Tween 80 has strong hydrophilicity and can be rapidly adsorbed to reduce interfacial tension, while its long polyoxyethylene chains form a hydration layer that provides steric hindrance. Polyglycerol-4 oleate exhibits strong lipophilicity, enabling the formation of a denser interfacial film. Its hydroxyl groups form hydrogen bonds with propylene glycol, enhancing film strength. The two interfaces are complementary: Tween 80 extends into the aqueous phase, providing steric hindrance, while polyglycerol-4 oleate anchors into the oil phase, further strengthening the film. Propylene glycol can regulate film flowability and reduce viscosity, improving nano-sizing effects. These three elements synergistically ensure efficient nanoemulsion formation and maintain long-term stability. The antioxidant stabilizer in the raw material is a 3:1 blend of vitamin E and citric acid. The conjugated triene structure of vitamin D3 is extremely sensitive to oxygen, necessitating the construction of a long-lasting antioxidant system. Vitamin E, as a fat-soluble chain-terminating antioxidant, directly blocks the oxidation chain reaction by donating hydrogen to lipid peroxidation free radicals through its phenolic hydroxyl groups. 3+ Cu 2+ The presence of metal ions interrupts the initiation pathway of the oxidation reaction, and the two mechanisms complement each other.
[0020] Anhydrous sodium carbonate was used to adjust the pH of the system to a weakly alkaline range of 6.5-7.5. This condition offers triple optimization for stability: the hydrophilic groups of the emulsifier maintain optimal conformation to ensure interfacial film strength; vitamin D3 is most stable in neutral to weakly alkaline environments; and the coexistence of divalent and trivalent dissociated forms of citric acid provides the strongest chelating ability for metal ions. As an inorganic base, anhydrous sodium carbonate exhibits superior thermal stability and chemical inertness compared to organic bases, does not undergo side reactions with other components in the system, and demonstrates high adjustment efficiency.
[0021] Compared with existing technologies, the nanoemulsion vitamin D3 drops and their preparation method provided by this invention have the following advantages: (1) This invention innovatively uses a compound of medium-chain triglycerides and ethyl oleate in a ratio of 2:1 to 3:1 as a composite oil phase. Compared with a single vegetable oil phase or a single MCT oil phase, it has both excellent fat solubility and water phase compatibility, which can significantly improve the solubility of vitamin D3 and reduce the interfacial tension between oil and water. The compound of polyglycerol-4 oleate and Tween 80 in a ratio of 1.5:1 to 2:1 is used as a composite emulsifier to synergistically achieve a high encapsulation effect of nanoemulsion. The compound of vitamin E and citric acid in a ratio of 3:1 is used as an antioxidant stabilizer. Vitamin E acts as a chain-terminating antioxidant to scavenge free radicals, and citric acid acts as a metal ion chelating agent to prevent metal ion catalytic oxidation. The two work together to achieve long-term antioxidant protection.
[0022] (2) This invention abandons the traditional single shear homogenization process and adopts a slow-drop high-shear coarse emulsion preparation and a two-stage gradient high-pressure micro-jet homogenization coupling process, coupled with nitrogen inert protection throughout the process, to achieve precise and controllable nanoemulsion particle size. The first-stage homogenization at 80-100MPa is used for preliminary refinement, and the second-stage homogenization at 140-160MPa is used to achieve nano-forming. The gradient pressure design is conducive to gradually refining the droplets and obtaining a narrower particle size distribution.
[0023] (3) The nano-emulsion droplets prepared by the present invention are a water-in-oil transparent nano system with excellent water solubility. They can be rapidly dissolved and absorbed across the membrane in the gastrointestinal environment. They do not separate or precipitate after being stored at room temperature and protected from light for 18 months, and the vitamin D3 retention rate is ≥96%.
[0024] (4) The process parameters of the present invention are mild and controllable, highly repeatable, require no complex equipment, have good batch product consistency, and can be directly applied to large-scale industrial aseptic production. Detailed Implementation
[0025] The present invention will be further described below through specific embodiments, but this is not a limitation of the present invention. Those skilled in the art can make various modifications or improvements based on the basic idea of the present invention, but as long as they do not depart from the basic idea of the present invention, they are all within the protection scope of the present invention.
[0026] All raw materials used in this invention are food and pharmaceutical grade, including: vitamin D3 content ≥99.0%, conforming to the standards of the Chinese Pharmacopoeia; medium-chain triglycerides are C8-C10 fatty acid triglycerides with a content ≥95%; ethyl oleate content ≥98%; polyglycerol-4 oleate HLB value 10-12; and Tween 80 HLB value approximately 15, conforming to pharmaceutical grade standards. The entire preparation process is carried out under light-protected and aseptic conditions.
[0027] Example 1: A method for preparing a nanoemulsion vitamin D3 drop, wherein the drop comprises the following raw materials in parts by weight: Vitamin D3 0.1 parts, compound oil phase 10 parts, compound emulsifier 6 parts, propylene glycol 2 parts, antioxidant stabilizer 0.5 parts, anhydrous sodium carbonate 0.2 parts, purified water to a total weight of 100 parts; The preparation method of this nanoemulsion vitamin D3 drops includes the following steps: S1. Preparation of the oil phase: The composite oil phase (medium-chain triglycerides and ethyl oleate in a mass ratio of 2.5:1) was preheated and stirred in a 42°C constant temperature water bath for 6 minutes at a stirring speed of 300 r / min. After the system was completely homogeneous and transparent, vitamin D3 and an antioxidant stabilizer (vitamin E and citric acid in a mass ratio of 3:1) were added. The mixture was stirred continuously at a constant temperature in the dark for 12 minutes until vitamin D3 was completely dissolved (no particulate matter was visually inspected), thus obtaining the oil phase. Nitrogen inert gas protection was used throughout the process. S2. Preparation of aqueous phase: Take purified water and heat it to 38°C. Add composite emulsifier (polyglycerol-4 oleate and Tween 80 in a mass ratio of 1.8:1), propylene glycol and anhydrous sodium carbonate. Stir at a constant temperature for 9 minutes at a stirring speed of 400 r / min until all excipients are completely dissolved, the system is clear and transparent, and the pH value is 7.2 to obtain the aqueous phase. S3. Preparation of crude emulsion: The oil phase prepared in step S1 is slowly added dropwise to the aqueous phase in step S2 over 18 min. During the dropwise addition, high-speed shear dispersion is used with a shearing speed of 13000 r / min. After the dropwise addition is completed, shearing is continued for 10 min to obtain crude emulsion. S4. Gradient homogenization and nano-sizing treatment: The crude emulsion is subjected to two-stage high-pressure micro-jet homogenization treatment. The first-stage homogenization pressure is 90MPa and the homogenization is performed twice. The second-stage homogenization pressure is 150MPa and the homogenization is performed three times. The system temperature is controlled at 32℃ during the homogenization process to obtain nano-emulsion stock solution. S5. Post-processing and filling: The nanoemulsion stock solution is placed in a light-proof, nitrogen-protected environment and naturally cooled to room temperature. It is then filtered through a 0.22μm sterile microporous membrane for sterilization and quantitative aseptic filling to obtain the finished nanoemulsion vitamin D3 drops.
[0028] Example 2: A method for preparing a nanoemulsion vitamin D3 drop, wherein the drop comprises the following raw materials in parts by weight: Vitamin D3 0.05 parts, compound oil phase 8 parts, compound emulsifier 4 parts, propylene glycol 1 part, antioxidant stabilizer 0.2 parts, anhydrous sodium carbonate 0.1 parts, purified water to a total weight of 100 parts; The preparation method of this nanoemulsion vitamin D3 drops includes the following steps: S1. Preparation of the oil phase: The composite oil phase (medium-chain triglycerides and ethyl oleate in a mass ratio of 2:1) was preheated and stirred in a 40°C constant temperature water bath for 5 minutes at a stirring speed of 300 r / min. After the system was completely homogeneous and transparent, vitamin D3 and an antioxidant stabilizer (vitamin E and citric acid in a mass ratio of 3:1) were added. The mixture was stirred continuously at a constant temperature in the dark for 15 minutes until vitamin D3 was completely dissolved (the absorbance was constant at 265 nm using ultraviolet spectrophotometry), thus obtaining the oil phase. Nitrogen inert gas protection was used throughout the process. S2. Preparation of aqueous phase: Take purified water and heat it to 35°C. Add composite emulsifier (polyglycerol-4 oleate and Tween 80 in a mass ratio of 1.5:1), propylene glycol and anhydrous sodium carbonate. Stir at a constant temperature for 8 minutes at a stirring speed of 400 r / min until all excipients are completely dissolved, the system is clear and transparent, and the pH value is 6.5 to obtain the aqueous phase. S3. Preparation of crude emulsion: The oil phase prepared in step S1 is slowly added dropwise to the aqueous phase in step S2 within 20 min. During the dropwise addition, high-speed shear dispersion is used with a shearing speed of 15000 r / min. After the dropwise addition is completed, shearing is continued for 8 min to obtain crude emulsion. S4. Gradient homogenization and nano-sizing treatment: The crude emulsion is subjected to two-stage high-pressure micro-jet homogenization treatment. The first-stage homogenization pressure is 80MPa and the homogenization is performed twice. The second-stage homogenization pressure is 140MPa and the homogenization is performed three times. The system temperature is controlled at 30℃ during the homogenization process to obtain nano-emulsion stock solution. S5. Post-processing and filling: The nanoemulsion stock solution is placed in a light-proof, nitrogen-protected environment and naturally cooled to room temperature. It is then filtered through a 0.22μm sterile microporous membrane for sterilization and quantitative aseptic filling to obtain the finished nanoemulsion vitamin D3 drops.
[0029] Example 3: A method for preparing a nanoemulsion vitamin D3 drop, wherein the drop comprises the following raw materials in parts by weight: Vitamin D3 0.2 parts, compound oil phase 15 parts, compound emulsifier 8 parts, propylene glycol 3 parts, antioxidant stabilizer 0.8 parts, anhydrous sodium carbonate 0.3 parts, purified water to a total weight of 100 parts; The preparation method of this nanoemulsion vitamin D3 drops includes the following steps: S1. Preparation of the oil phase: The composite oil phase (medium-chain triglycerides and ethyl oleate in a mass ratio of 3:1) was preheated and stirred in a 45°C constant temperature water bath for 8 minutes at a stirring speed of 300 r / min. After the system was completely homogeneous and transparent, vitamin D3 and an antioxidant stabilizer (vitamin E and citric acid in a mass ratio of 3:1) were added. The mixture was stirred continuously at a constant temperature in the dark for 10 minutes until vitamin D3 was completely dissolved (no particulate matter was visually inspected), thus obtaining the oil phase. Nitrogen inert gas protection was applied throughout the process. S2. Preparation of aqueous phase: Take purified water and heat it to 40°C. Add composite emulsifier (polyglycerol-4 oleate and Tween 80 in a mass ratio of 2:1), propylene glycol and anhydrous sodium carbonate. Stir at a constant temperature for 10 minutes at a stirring speed of 400 r / min until all excipients are completely dissolved, the system is clear and transparent, and the pH value is 7.5 to obtain the aqueous phase. S3. Preparation of crude emulsion: The oil phase prepared in step S1 is slowly added dropwise to the aqueous phase in step S2 within 15 min. During the dropwise addition, high-speed shear dispersion is used with a shearing speed of 12000 r / min. After the dropwise addition is completed, shearing is continued for 12 min to obtain crude emulsion. S4. Gradient homogenization and nano-sizing treatment: The crude emulsion is subjected to two-stage high-pressure micro-jet homogenization treatment. The first-stage homogenization pressure is 100MPa and the homogenization is performed twice. The second-stage homogenization pressure is 160MPa and the homogenization is performed three times. The system temperature is controlled at 35℃ during the homogenization process to obtain nano-emulsion stock solution. S5. Post-processing and filling: The nanoemulsion stock solution is placed in a light-proof, nitrogen-protected environment and naturally cooled to room temperature. It is then filtered through a 0.22μm sterile microporous membrane for sterilization and quantitative aseptic filling to obtain the finished nanoemulsion vitamin D3 drops.
[0030] Comparative Example 1: Compared with Example 1, the difference in Comparative Example 1 is that only the complex oil phase is replaced with an equal amount of single medium-chain triglycerides, while the other raw material ratios and preparation processes are the same as in Example 1.
[0031] Comparative Example 2: Compared with Example 1, the difference in Comparative Example 2 is that only the composite emulsifier is replaced with an equal amount of Tween 80, while the other raw material ratios and preparation processes are the same as in Example 1.
[0032] Comparative Example 3: Compared with Example 1, the difference in Comparative Example 3 is that the antioxidant stabilizer component was removed (i.e., vitamin E and citric acid were not added), while the remaining raw material ratios and preparation processes were the same as in Example 1.
[0033] Comparative Example 4: Compared with Example 1, the difference in Comparative Example 4 is that the two-stage gradient high-pressure microjets homogenization step is omitted, and only high-speed shearing at 13000 r / min for 20 min is used to prepare the emulsion. The remaining raw material ratios and steps are the same as in Example 1.
[0034] Comparative Example 5: Compared with Example 1, the difference of Comparative Example 5 is that the nitrogen inert gas protection step throughout the process was omitted, and it was prepared under open environmental conditions. The remaining raw material ratios and processes are the same as those in Example 1.
[0035] Comparative Example 6: We selected mainstream oil-soluble vitamin D3 drops available on the market as the control sample (product name: Hanwei Vitamin D Drops, manufacturer: Huaxia Guoyao (Heze) Pharmaceutical Co., Ltd.).
[0036] Experimental studies were conducted on the vitamin D3 drops obtained in Examples 1-3 and Comparative Examples 1-6 of the present invention: I. Testing Method: (1) Measurement of average particle size and PDI: Dynamic light scattering particle size analyzer (DLS) was used. The samples were appropriately diluted with purified water to a suitable concentration, equilibrated at 25℃ for 5 min, and then measured. Each sample was measured in parallel 3 times, and the average value was recorded. The average particle size (z-average) and polydispersity index (PDI) were recorded.
[0037] (2) Determination of vitamin D3 encapsulation efficiency: Ultrafiltration centrifugation was used. 1.0 mL of the nanoemulsion sample was placed in an ultrafiltration centrifuge tube (molecular weight cutoff 10 kDa) and centrifuged at 4000 rpm for 30 min. The vitamin D3 content in the filtrate and the original solution was determined using high-performance liquid chromatography (HPLC). Chromatographic conditions: C18 column, mobile phase: methanol:water = 95:5, detection wavelength 265 nm, flow rate 1.0 mL / min, column temperature 30 °C. The encapsulation efficiency was calculated using the following formula: Encapsulation efficiency (%) = (1-C) 滤液 / C 原液 ) × 100%; Where C 滤液 C represents the total concentration of the drug in the drug delivery system. 原液 This represents the concentration of the free drug.
[0038] (3) Determination of vitamin D3 retention rate: High-performance liquid chromatography (HPLC) was used, under the same chromatographic conditions as above. Vitamin D3 content was determined at 0 months and 18 months of storage, and the retention rate was calculated using the following formula: Retention rate (%) = (C 18月 / C 0月 ) × 100%; Among them, C 0月 The vitamin D3 content was detected immediately after the preparation of the nanoemulsion vitamin D3 drops. C 18月 The vitamin D3 content of the drops was measured after 18 months of storage at room temperature and away from light.
[0039] (4) In vitro simulated absorption rate determination: A Caco-2 cell monolayer model was used. Caco-2 cells were seeded in Transwell chambers and cultured for 21 days to form a dense monolayer cell membrane. The transmembrane resistivity was measured to be ≥500 Ω·cm. 2 The sample was then prepared for later use. After diluting the sample with HBSS buffer, it was added to the top side (AP side) and incubated at 37°C for 2 hours. The sample from the base side (BL side) was collected, and the vitamin D3 content was determined by HPLC. The apparent permeability coefficient P was calculated. app The relative absorption rate was calculated using commercially available oil-soluble vitamin D3 drops as a control.
[0040] (5) Zeta potential measurement: Electrophoretic light scattering method was used. After the samples were appropriately diluted with purified water, they were measured at 25℃ using a Zeta potential analyzer. Each sample was measured in triplicate, and the average value was taken.
[0041] (6) Evaluation of appearance stability: Visually inspect the sample to see if it is clear and transparent, without layering, sedimentation, or discoloration.
[0042] II. Test Results: The results are shown in Tables 1 and 2.
[0043] Table 1 shows the data results for the product's particle size, encapsulation efficiency, etc.
[0044] Table 2 shows the product's appearance stability results:
[0045] As shown in Tables 1 and 2, the nanoemulsion vitamin D3 drops prepared in Examples 1-3 of this invention all exhibit excellent comprehensive performance. Regarding particle size control, the average particle size of the three examples remained stable in the range of 22.3-38.5 nm, with PDI values all ≤0.14, indicating that the nanoemulsion droplets are highly uniform and concentrated, achieving precise controllability at the nanoscale. In terms of encapsulation efficiency, the encapsulation rate of each example was ≥98.5%, proving that the formulation system of composite oil phase and composite emulsifier can efficiently encapsulate vitamin D3 within the lipid core of the nanoemulsion droplets, resulting in extremely low free drug levels. Regarding long-term stability, after 18 months of storage at 25℃±2℃ in the dark, the vitamin D3 retention rate of each example was ≥96.2%, and the appearance remained clear and transparent, without stratification or precipitation, demonstrating excellent shelf-life stability. Regarding in vitro absorption, the simulated in vitro absorption rate of each example reached 90.8%-93.5%, a significant improvement compared to traditional oil-soluble formulations.
[0046] Comparing the various embodiments, Example 2 showed slightly better performance than Examples 1 and 3, possibly due to the lower oil phase and emulsifier concentrations, which facilitated the formation of smaller droplets. However, all three examples achieved the expected nanoemulsion performance indicators, demonstrating that the technical solution of this invention can stably achieve its purpose within a wide range of formulations and exhibits good formulation robustness. The comparative example data shows that the raw materials and preparation method in this invention are interdependent and synergistic, jointly achieving a comprehensive technical effect of particle size <40nm, PDI≤0.15, encapsulation efficiency ≥98.5%, 18-month retention rate ≥96%, and absorption rate more than 4 times higher than traditional formulations.
[0047] III. Stability tests were conducted on the products obtained in Examples 1-3 of this invention: (1) Long-term stability test: The samples from Examples 1-3 were stored at 25℃±2℃ under light-protected conditions for 18 months, and samples were taken for testing at 0, 3, 6, 9, 12, and 18 months. The results showed that the samples from all examples remained clear and transparent during the 18-month storage period, without layering, precipitation, or discoloration, and the vitamin D3 retention rate was ≥96%.
[0048] (2) Accelerated stability test: Samples from Examples 1-3 were stored at 40℃±2℃ and 75%RH±5%RH for 6 months, and samples were taken for testing at 0, 1, 2, 3, and 6 months. The results showed that the samples from each example remained clear and transparent after 6 months of accelerated testing, and the vitamin D3 retention rate was ≥92%.
[0049] (3) Low temperature stability test: The samples from Examples 1-3 were stored at 4℃±2℃ for 6 months, and samples were taken and tested periodically. The results showed that the samples from each example remained clear and transparent after being stored at low temperature and then restored to room temperature, with no crystallization and no significant change in particle size.
[0050] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the invention. Any person skilled in the art can modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in the present invention should still be covered by the claims of the present invention.
Claims
1. A method for preparing nanoemulsion vitamin D3 drops, characterized in that, The drops comprise the following raw materials in parts by weight: Vitamin D3 0.05-0.2 parts, compound oil phase 8-15 parts, compound emulsifier 4-8 parts, co-emulsifier 1-3 parts, antioxidant stabilizer 0.2-0.8 parts, pH adjuster 0.1-0.3 parts, purified water to 100 parts; The preparation method of this nanoemulsion vitamin D3 drops includes the following steps: S1. Preparation of oil phase: The composite oil phase is preheated and stirred in a constant temperature water bath at 40-45℃ for 5-8 minutes at a stirring speed of 300 r / min. After the system is completely homogeneous and transparent, vitamin D3 and antioxidant stabilizer are added, and the mixture is stirred continuously at a constant temperature in the dark for 10-15 minutes until vitamin D3 is completely dissolved to obtain the oil phase. Nitrogen inert gas protection is used throughout the process. S2. Preparation of aqueous phase: Take purified water and heat it to 35-40℃. Add composite emulsifier, co-emulsifier and pH adjuster. Stir at a constant temperature for 8-10 minutes at a stirring speed of 400r / min until all excipients are completely dissolved and the system is clear and transparent to obtain the aqueous phase. S3. Preparation of crude emulsion: The oil phase prepared in step S1 is slowly added dropwise to the aqueous phase in step S2 over a period of 15-20 min. During the addition process, high-speed shear dispersion is used with a shearing speed of 12000-15000 r / min. After the addition is completed, shearing is continued for 8-12 min to obtain crude emulsion. S4. Gradient homogenization and nano-sizing treatment: The crude emulsion is subjected to two-stage high-pressure micro-jet homogenization treatment. The first-stage homogenization pressure is 80-100MPa and the homogenization is performed twice. The second-stage homogenization pressure is 140-160MPa and the homogenization is performed three times. The system temperature is controlled at 30-35℃ during the homogenization process to obtain nano-emulsion stock solution. S5. Post-processing and filling: The nanoemulsion stock solution is placed in a light-proof, nitrogen-protected environment and naturally cooled to room temperature. It is then filtered through a 0.22μm sterile microporous membrane for sterilization and quantitative aseptic filling to obtain the finished nanoemulsion vitamin D3 drops.
2. The preparation method according to claim 1, characterized in that, The composite oil phase is a mixture of medium-chain triglycerides and ethyl oleate in a mass ratio of 2:1 to 3:
1.
3. The preparation method according to claim 1, characterized in that, The composite emulsifier is a mixture of polyglycerol-4 oleate and Tween 80 in a mass ratio of 1.5:1 to 2:
1.
4. The preparation method according to claim 1, characterized in that, The emulsifier is propylene glycol.
5. The preparation method according to claim 1, characterized in that, The antioxidant stabilizer is a mixture of vitamin E and citric acid in a mass ratio of 3:
1.
6. The preparation method according to claim 1, characterized in that, The criteria for determining complete dissolution of vitamin D3 in step S1 are: no particulate matter is visible upon visual inspection, or the absorbance is constant when detected by ultraviolet spectrophotometry at 265 nm.
7. The preparation method according to claim 1, characterized in that, The pH adjuster is anhydrous sodium carbonate, and the amount of anhydrous sodium carbonate used is to adjust the pH of the system to 6.5-7.
5.
8. The preparation method according to claim 1, characterized in that, The finished nanoemulsion vitamin D3 drops have an average particle size of 20-40 nm, a particle size distribution index (PDI) ≤ 0.15, and a vitamin D3 encapsulation rate ≥ 98.5%.
9. The preparation method according to claim 1, characterized in that, The finished nanoemulsion vitamin D3 drops, when stored at 25℃±2℃ in the dark for 18 months, retain ≥96% of the vitamin D3.
Citation Information
Patent Citations
Vitamin D nano-emulsion and preparation method thereof
CN103520102A
Vitamin d micro-emulsions and uses thereof
CN113498344A
